Effects of tool path strategies on surface roughness in high speed milling - Abdul Rashid, Muhammad (2012)
In this project, two type of tool path strategies have been selected which are helical and back and forth tool path in order to determine the effects of both tool path strategies on surface roughness. The effects of the feed rate, cutting speed, and depth of cut on surface roughness were determined. Taguchi method was employed in order to optimize the machining parameters. The optimum machining parameter combination was determined by using analysis of signal-to-noise (S/N) ratio. The impact of the machining parameters on the surface roughness was determined by the use of analysis of variance (ANOVA). Measurement of surface roughness has indicated that helical has lowest surface roughness compare to back and forth tool path. Results from ANOVA also proved that helical tool path has significant impact on surface roughness. Furthermore, S/N ratio shows that each type of tool path has different combination of optimum machining parameters. From this project, it has been learned that helical tool path is better cutting tool path to be used in machining operation. This project would help engineer and machinist to select the best pocketing tool path for their product.